UNDERWATER IMAGE ENHANCEMENT THROUGH DEHAZING AND COLOR CORRECTION TECHNIQUES (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Underwater photography and videography suffer from significant challenges due to the inherent properties of water, such as light absorption, scattering, and color distortion. When capturing images or videos underwater, the medium's particulate matter and water molecules cause haze and loss of color fidelity, resulting in poor visual quality and reduced visibility. To address these issues and improve the overall quality of underwater imagery, researchers have developed various image enhancement techniques that aim to dehaze the images and correct color distortions. The traditional approach to underwater image enhancement involved simple post-processing methods, such as contrast stretching and histogram equalization. While these techniques might help to some extent, they often fail to produce satisfactory results due to the complex and non-linear nature of underwater light attenuation and scattering. Moreover, these methods are not specifically designed for addressing the unique challenges posed by underwater environments, leading to limited improvements in image quality. Therefore, the need for effective underwater image enhancement techniques arises from several factors such as, underwater imagery is crucial in various fields, including marine biology, underwater exploration, environmental monitoring, and underwater archaeology. In addition, high-quality images are essential for accurate data analysis and interpretation. Further, an improved underwater image quality aids in enhancing the capabilities of underwater robotics, surveillance systems, and underwater imaging devices. Thus, this project presents an innovative and comprehensive approach to address the challenges associated with underwater imagery. The study proposes a novel combination of dehazing, and color correction techniques tailored specifically for the unique characteristics of underwater environments.